Perioperative Hypoxemia and Postoperative Respiratory Events in Infants with Hypertrophic Pyloric Stenosis - van den Bunder, Fenne A.I.M.; Stevens, Markus F.; van Woensel, Job B.M.; van de Brug, Tim; van Heurn, L.W Ernest; Derikx, Joep P.M. (European Journal of Pediatric Surgery, 2023)
Background Normalization of metabolic alkalosis is an important pillar in the treatment of infantile hypertrophic pyloric stenosis (IHPS) because uncorrected metabolic alkalosis may lead to perioperative respiratory events. However, the evidence on the incidence of respiratory events is limited. We aimed to study the incidence of peroperative hypoxemia and postoperative respiratory events in infants undergoing pyloromyotomy and the potential role of metabolic alkalosis.Materials and Methods We retrospectively reviewed all patients undergoing pyloromyotomy between 2007 and 2017. All infants received intravenous fluids preoperatively to correct metabolic abnormalities close to normal. We assessed the incidence of perioperative hypoxemia (defined as oxygen saturation [SpO2] < 90% for > 1min) and postoperative respiratory events. Additionally, the incidence of difficult intubations was evaluated. We performed a multivariate logistic regression analysis to evaluate the association between admission or preoperative serum pH values, bicarbonate or chloride, and peri- and postoperative hypoxemia or respiratory events.Results Of 406 included infants, 208 (51%) developed 1 or more episodes of hypoxemia during the perioperative period, of whom 130 (32%) experienced it during induction, 43 (11%) intraoperatively, and 112 (28%) during emergence. About 7.5% of the infants had a difficult intubation and 17 required more than 3 attempts by a pediatric anesthesiologist. Three patients developed respiratory insufficiency and 95 postoperative respiratory events were noticed. We did not find a clinically meaningful association between laboratory values reflecting metabolic alkalosis and respiratory events.Conclusions IHPS frequently leads to peri- and postoperative hypoxemia or respiratory events and high incidence of difficult tracheal intubations. Preoperative pH, bicarbonate, and chloride were bad predictors of respiratory events.
Keywords: hypertrophic pyloric stenosis; pyloromyotomy; hypoxemia; apnea; anesthesia